PENGARUH VARIASI CAMPURAN TEPUNG DAUN KELOR (Moringaoleifera L) DAN BEKATUL TERHADAP PERTUMBUHAN AYAM KAMPUNG (Gallus-gallus domesticus. Var. Ayam Joper) SEBAGAI SUMBER BELAJAR BIOLOGI - Wisca Febriana; Agus Sutanto; Suharno Zen (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The research about the mixture of moringa leaf flour and rice bran on the growth of orgainic chicken on Joper chicken. var as a source of learning biology aims to determine the effect of feed from the mixture of moringa leaf flour (Moringa oleifera L) and rice bran on the growth of organic chickens (Gallus-gallus domesticus L. Joper chicken. var), then to find out certain variations of the mixture of moringa leaf flour (Moringa oleifera L) and rice bran which gives the best influence and to make posters that are used as a source of high school biology learning. The method used is a completely randomized design (CRD), experiments conducted with 3 treatments and 1 control. Control (0% moringa leaf flour), P1 (2.5% moringa leaf flour), P2 (5% moringa leaf flour) and P3 (7.5% moringa leaf flour). The parameters observed were weight, length, and diameter of the joper body.The results of the study were tested using a non-parametric statistical test or commonly called the kruskal wallis test. Kruskal wallis test results on chicken weight obtained X2value 4.09 <X2table 14.07 at α 0.05 means Ho is accepted, length measurements obtained results X2value = 3.61 <X2table = 14.07 at α 0.05 means Ho is accepted, diameter measurements obtained results X2 value = 4.2 <X2 table = 14.07 at α 0.05 means Ho is accepted.The conclusion from this study was the feed from the mixture of moringa leaf flour and rice bran did not have a significant effect on the growth of joper. The results of the used ranking from 5% Moringa leaf flour gave the best effect for weight gain of joper. Based on the results of the validation of learning resources shows that learning resources in the form of posters that are made were feasible to be used as a source of learning biology for high school students.Kata kunci: super java chicken, Indigofera, alternative feed, poster learning resources